Extra-Class Reading at the Lessons of Literature in the Middle Classes - Buranova Lily Shavkatovna (Peerian Journals Publishing, 2022)
the article discusses the feasibility of extracurricular reading in literature lessons in the middle school. The problem of the fact that teenagers began to read less due to computerization, and ways to solve this issue are analyzed. Thoughts are expressed that in the methodology of teaching literature, the position that literature lessons associated with extracurricular reading more actively contribute to the development of reading independence of students is firmly established.
Keywords: out-of-class reading; methods; techniques; debate